The Role and Importance of English for Specific Purposes (ESP) in Modern Education (Ta'limning zamonaviy transformatsiyasi, 2024)
In today's globalized world, where English is the language of choice for many academic and professional fields, English for Specific Purposes (ESP) has become an essential component of language education. ESP courses are designed to satisfy the unique requirements of students studying in several disciplines, including law, business, engineering, and medical. In order to address the function and significance of ESP in contemporary education, this essay looks at its applicability, usefulness, and suitability for addressing 21st-century professional expectations. Bugungi globallashgan dunyoda ingliz tili ko'plab akademik va professional sohalar uchun asosiy tilga aylangan bir paytda, Kasbga yo‘naltirilgan ingliz tili (ESP) til o'rganishning juda muhim qismiga aylandi. Kasbga yo‘naltirilgan ingliz tili kurslari huquq, biznes, muhandislik, tibbiyot kabi bir nechta yo'nalishlarda tahsil olayotgan talabalarni o'ziga xos ehtiyojlarini qondirish uchun ishlab chiqilgan. Ushbu maqola zamonaviy ta'limda Kasbga yo‘naltirilgan ingliz tilining o'rni va ahamiyatini, uning qo'llanishi, foydaliligi va XXI asr professional talablariga mosligini tahlil qiladi.В современном глобализированном мире, где английский язык является предпочтительным во многих академических и профессиональных сферах, английский для специальных целей (ESP) стал неотъемлемой частью языкового образования. Курсы ESP разрабатываются для удовлетворения уникальных потребностей студентов, обучающихся в различных дисциплинах, таких как право, бизнес, инженерия и медицина. Эта статья рассматривает роль и значение ESP в современном образовании, а также его применимость, полезность и соответствие профессиональным требованиям XXI века.